SEMANTIC CLUSTERING WITH CONTEXT ONTOLOGY FOR INFORMATION RETRIEVAL SYSTEM - lai, thinn (International Journal of Computer (IJC), 2013)
Nowadays, there are so many increasing amount of information within world-wide web. For these increasing amounts of information, we need efficient and effective index structure when we have to find needed information. Most indexing techniques directly matched terms from the document and terms from query. But there is a problem when matching. That is most system doesn’t consider the meaning of the words. A word can have more than one meaning. But most systems didn’t consider the context (multiple meaning of a word). This paper presents how to construct an index structure using SSTC and context ontology that provides multiple meanings of a word. Context provides extra information to improve search result relevance. This paper produces context semantic cluster to provide indexing of search engine.